FROM GROWTH TO DEVELOPMENT OF INDIAN E-FOODS DELIVERY SERVICES – A STUDY IN MADURAI CITY - Kajapriya , R.; Ratheka, R. (International Journal of Psychosocial Rehabilitation, 2020)
Internet businesses are navigating into many Industries and now it changed the brick and mortar system of restaurants foods into E-foods that allows the customers to take their favourite restaurant foods at their place without move. E-foods delivery businesses gets commercialized not only in the metro or cosmopolitan cities but also in tier 2 and tier 3 cities. Digital services on the other hand are services that are anything that can be delivered through an information infrastructure such as the internet, in various forms i.e. applications, web pages, social media, etc. There are several mobile applications which enable the consumers to order foods online from various restaurants and the delivery of foods can be managed by the application providers. This research is to understand the functions of E-foods delivery services, to identify the factors which influence the consumer to order food online, to know the consumer preferences on online food ordering services provider, to analyse the reason that prevents consumers to take E-foods and the overall satisfaction of consumers towards E-foods delivery services.